More than a dance: The production of sexual health risk in the exotic dance clubs in Baltimore, USA - Sherman, Susan G. (2011)
Women who exchange sex for money, drugs, or goods are disproportionately infected with HIV and have high rates of illicit drug use. A growing body of research has underscored the primacy of environmental factors in shaping individual behaviors. HIV/STI rates among sex workers are influenced by environmental factors such as the physical (e.g., brothel) and economic (e.g., increased pay for unsafe sex) context in which sex work occurs. Exotic dance clubs (EDCs) could be a risk environment that is epidemiologically significant to the transmission of HIV/STIs among vulnerable women, but it is a context that has received scant research attention. This study examines the nature of the physical, social, and economic risk environments in promoting drug and sexual risk behaviors. Structured observations and semi-structured qualitative interviews (N=40) were conducted with club dancers, doormen, managers, and bartenders from May through August, 2009. Data were analyzed inductively using the constant comparative method common to grounded theory methods. Atlas-ti was used for data analysis. Dancers began working in exotic dance clubs primarily because of financial need and lack of employment opportunities, and to a lesser extent, the need to support illicit drug habits. The interviews illuminated the extent to which the EDCs’ physical (e.g., secluded areas for lap dances), economic (e.g., high earnings from dancers selling sex), and social (e.g., prevailing social norms condoning sex work) environments facilitated dancers’ engaging in sex work. Drug use and alcohol use were reported as coping mechanisms in response to these stressful working conditions and often escalated sexual risk behaviors. The study illuminated characteristics of the environment that should be targeted for interventions.